2016
DOI: 10.1186/s12950-016-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin along with antibiotics balances reactive oxygen species and inflammatory cytokines and controls Staphylococcus aureus infection by boosting murine macrophage function and regulates inflammation

Abstract: BackgroundMacrophages serve as intracellular reservoirs of S. aureus. Recent in vitro studies have confirmed high level resistance by S. aureus to macrophage mediated killing and the intracellular persistence of Staphylococci may play an important role in the pathogenesis. Since this localization protects them from both cell-mediated and humoral immune responses, therefore, a successful anti-staphylococcal therapy should include the elimination of intracellular bacteria, further protecting the host cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 70 publications
(81 reference statements)
1
43
0
Order By: Relevance
“…As mentioned above, RF plays a crucial role in Nox2. The experiment of Dey and Bishayi [49] showed that RF pre-treated macrophages lead to elevated levels of H2O2, O2 -as well as ROS and cause direct oxidative damage to many pathogens ( Figure 5). RF along with antibiotics balances ROS and inflammatory cytokines and controls S. aureus infection by boosting murine macrophage function and regulates inflammation [49].…”
Section: Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned above, RF plays a crucial role in Nox2. The experiment of Dey and Bishayi [49] showed that RF pre-treated macrophages lead to elevated levels of H2O2, O2 -as well as ROS and cause direct oxidative damage to many pathogens ( Figure 5). RF along with antibiotics balances ROS and inflammatory cytokines and controls S. aureus infection by boosting murine macrophage function and regulates inflammation [49].…”
Section: Cancermentioning
confidence: 99%
“…In terms of the efficacy of treatment with RF in combination with antibiotics (ampicillin [48,49], azithromycin [50], Ciprofloxacin [49]) or amino acids [8] on septic arthritis, RF has been reported as causing an increase in the survival rate of mice [50].…”
Section: Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In a staphylococcal infection setting, riboflavin has demonstrated its anti-inflammatory property through reductions in NF-κB, COX2 (cyclooxygenase 2), TNF-α, NO, IL-1β (interleukin 1 beta) reducing iNOS (inducible NO synthase) synthesis, as well as an elevation in anti-inflammatory cytokine IL-10 (interleukin 10), and modulation of MCP-1 (monocyte chemoattractant protein 1) function, a potent chemoattractant (34). …”
Section: Riboflavin Ameliorates Oxidative Stress Mitochondrial Dysfumentioning
confidence: 99%